Milk Consumption Correlates with Body Height in Children - Evan Tirtasaputra; Grace Puspasari; Teresa Lucretia (Journal of Medicine and Health, 2019)
Growth in children is very important because it affects a person's height as an adult.Qualified and adequate nutrition play a significant role in growth. Adequate milk consumptioncan affect bone growth which ultimately affects height and helps reduce the risk of bone loss.The purpose of this study was to determine the correlation between milk consumption andheight in children. This study is an analytic observational study, involving 126 subjects aged 6-9 years from an elementary school in Bandung. The sample was taken by whole samplingtechnique. Data collection was carried out using questionnaires and height measurements. Thedata was analyzed using the Gamma correlation test. The statistical results showed a significantrelationship between the frequency of milk consumption and height (p = 0.044) with a mediumcorrelation coefficient (r = 0.430) and a positive correlation direction which meant an increasein the frequency of milk consumption along with the increasing height in children aged 6-9years. We concluded that milk consumption correlates with body height in children.Keywords: milk consumption, body height, children, correlation